Cytotoxicity Assessment of Surface-Modified Magnesium Hydroxide Nanoparticles (2022)
Magnesium-based nanoparticles have shown promise inregenerative therapies in orthopedics and the cardiovascular system.Here, we set out to assess the inﬂuence of diﬀerently functionalized Mgnanoparticles on the cellular players of wound healing, the ﬁrst step inthe process of tissue regeneration. First, we thoroughly addressed thephysicochemical characteristics of magnesium hydroxide nanoparticles,which exhibited low colloidal stability and strong aggregation in cellculture media. To address this matter, magnesium hydroxide nano-particles underwent surface functionalization by 3-aminopropyltriethox-ysilane (APTES), resulting in excellent dispersible properties in ethanoland improved colloidal stability in physiological media. The latter wasdetermined as a concentration- and time-dependent phenomenon.There were no signiﬁcant eﬀects on THP-1 macrophage viability up to1.500 μg/mL APTES-coated magnesium hydroxide nanoparticles.Accordingly, increased media pH and Mg 2+ concentration, the nanoparticles dissociation products, had no adverse eﬀects ontheir viability and morphology. HDF, ASCs, and PK84 exhibited the highest, and HUVECs, HPMECs, and THP-1 cells the lowestresistance toward nanoparticle toxic eﬀects. In conclusion, the indicated high magnesium hydroxide nanoparticles biocompatibilitysuggests them a potential drug delivery vehicle for treating diseases like ﬁbrosis or cancer. If delivered in a targeted manner, cytotoxicnanoparticles could be considered a potential localized and speciﬁc prevention strategy for treating highly prevalent diseases likeﬁbrosis or cancer. Looking toward the possible clinical applications, accurate interpretation of in vitro cellular responses is thekeystone for the relevant prediction of subsequent in vivo biological eﬀects.